WEIMAR REPUBLIC IN THE DIALECTIC THEOLOGY OF FRIEDRICH GOGARTEN - N. Virt (Гуманитарные и юридические исследования)
The article is devoted to the consideration of the views of the Lutheran theologian Friedrich Gogarten on the republican system of Weimar Germany. At the beginning of the article, the reasons for the formation of dialectical theology in Germany of the 1920s are revealed. After the establishment of the republican form of government, the situation of the Protestant churches in Germany changes significantly. Their role and influence are weakening, and the number of parishioners is decreasing. The process of change affects not only churches as structural entities, but also theological thought. The article highlights the main reasons for the transition from liberal theology of the XIX to a new dialectical theology. One of the most important reasons for the changes in Protestant theology was the consequences of the First World War, which caused a pan-European cultural crisis. Also, the ideas of C. Bart influenced the formation of a new theology. Of decisive importance was the inability of liberal theology to ind a way out of the current cultural crisis. The features of the theological ideas of the Lutheran theologian F. Gogarten, which are formed under the influence of theology of the crisis, are examined. F. Gogarten's contribution to the development of dialectical theology during the 1920s and the first half of the 1930s is noted. The roots of his political ideas lie in a new interpretation of the views on the structure of the state and society, which were formed by Martin Luther and other church reformers. Based on a review of the political concepts of F. Gogarten, his attitude to Weimar Germany is revealed. The theologian sees anarchism in the republican system, which contradicts the fundamental foundations of Christianity. Germany in the 1920s appears in his writings as a country compelled to search for new ways of government. F. Gogarten sees one of the options as the establishment of a dictatorship to suppress the anarchist tendencies of German society. In conclusion, the reasons for F. Gogarten's support of the national socialist dictatorship during the 1930s are analyzed and his collaboration with the protestant movement of "German Christians".